2007
DOI: 10.1128/aac.01544-06
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinins Inhibit Trypanosoma cruzi and Trypanosoma brucei rhodesiense In Vitro Growth

Abstract: Artemisinin compounds inhibit in vitro growth of cultured Trypanosoma cruzi and Trypanosoma brucei rhodesiense at concentrations in the low micromolar range. Artemisinin also inhibits calcium-dependent ATPase activity in T. cruzi membranes, suggesting a mode of action via membrane pumps. Artemisinins merit further investigation as chemotherapeutic options for these pathogens.Diseases caused by insect-borne trypanosomatid parasites are a significant and neglected public health problem worldwide. Chagas' disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 22 publications
1
78
0
3
Order By: Relevance
“…These include repellency against beetles (16), larvicidal activity against Anopheles stephensi (17), insecticidal activity against elm leaf beetle (18), and use as an acaricide (19). Moreover, AN and its derivatives have effects on a number of viruses (20), a variety of human cancer cell lines (20,21), and several neglected tropical parasitic diseases including schistosomiasis (22), leishmaniasis (23,24), New-and Old-World trypanosomiases (25), and some livestock diseases (26).…”
Section: Resultsmentioning
confidence: 99%
“…These include repellency against beetles (16), larvicidal activity against Anopheles stephensi (17), insecticidal activity against elm leaf beetle (18), and use as an acaricide (19). Moreover, AN and its derivatives have effects on a number of viruses (20), a variety of human cancer cell lines (20,21), and several neglected tropical parasitic diseases including schistosomiasis (22), leishmaniasis (23,24), New-and Old-World trypanosomiases (25), and some livestock diseases (26).…”
Section: Resultsmentioning
confidence: 99%
“…Together with its semi-synthetically prepared derivatives such as dihydroartemisinin, artesunate and artemether, artemisinin has also displayed unique pharmacological activities against a wide range of parasitic organisms including bacteria (Bone and Morgan, Brisibe et al 9587 1992) such as Enterobacter species, Klebsiella pneumoniae, Streptococcus faecalis, Staphylococcus aureus, Shigella dysenteriae, Escherichia coli and Pneumocystis carinii (Chen et al, 1994), an opportunistic pathogen which causes pneumonia in HIV/AIDS and other immune-compromised patients. Recent studies have demonstrated that artemisinin derivatives are equally potent and efficacious against several other common infectious parasites of man including Toxoplasma gondii (Jones-Brando et al, 2006) which causes toxoplasmosis that is responsible for behavioral abnormalities in patients, Trypanosoma and Schistosoma species (Mishina et al, 2007;Utzinger et al, 2001) that are responsible for human trypanosomiasis or 'sleeping sickness' and schistosomiasis, respectively. Artemisinin derivatives are also effective against some other pathogens including those responsible for cryptosporidiosis, amoebiasis, giardiasis, clonorchiasis and leishmaniasis (Ma et al, 2004;Yang and Liew, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Besides its antimalarial activity, artemisinin has proved effective against cancer (Posner et al, 1999;Singh and Lai, 2004;Efferth, 2005), Eimeria spp., Babesia spp., Leishmania spp., Neospora caninum, Trypanosoma brucei rhodesiense (Mishina et al, 2007), and Schistosoma spp. (Utzinger et al, 2001;Xiao et al, 2004), the latter living in the circulatory system of the host.…”
Section: Introductionmentioning
confidence: 99%